Ni-supported catalysts for ethanol steam reforming: effect of the solvent and metallic precursor in catalyst preparation - Villagran Olivares, Alejandra Catalina (2017)
Ethanol steam reforming was studied over Ni/MgAl2O4–CeO2 catalysts. The catalysts were prepared using different impregnation media (ethanol or water) and Ni precursors (nitrate or acetate). The use of an alcoholic solution did not affect the specific surface area, but promoted the NiO formation reducible at lower temperature affecting the Ni-support interactions and the Ce3+/Ce4+ initial ratios. All catalysts were highly active in the reforming reaction of ethanol with a high initial conversion of ethanol under more severe conditions than those commonly used in literature. The best catalytic behavior was found over the catalyst prepared from an ethanolic solution of Ni(NO3)2. This sample showed a high Ce3+/Ce4+ ratio, an adequate interaction Ni-support and an average Ni diameter around 28 nm. This catalyst was stable under the reforming conditions used in this work: initial ethanol concentration: 9.4%, reaction temperature: 650 °C, W/F = 49 g min molC2H5OH-1 and reaction time: 40 h. The ethanol conversion was almost complete with H2 selectivity around 78%.